Le «heureux hasard»: A propos de la redécouverte de la Carta marina - Balzamo, Elena (Journal of Northern Studies, 2008)
The article, a “case study”, deals with questions concerning the fate of the two known copies of the famous Carta Marina (1539), the earliest map of the Nordic countries that gives details and presents geographical entities in a recognisable way. It was created by the last Swedish Catholic archbishop Olaus Magnus (1492–1557) during his long exile, first in Poland (Danzig), then in Italy (Venice, Trento, Rome). The map was printed in Venice from nine woodcut blocks; the resulting print measures 1.70 m x 1.25 m but the number of printed copies remains unknown. The map was accompanied by a separately printed commentary by Olaus Magnus, who, some years later, wrote a book on the same subject: Historia de gentibus septentrionalibus, Rome 1555 [‘A Description of the Northern Peoples’]. The latter is generally considered a larger commentary on the map and remains, together with the map itself, the main source of information about the Nordic countries in the sixteenth century. At the end of the seventeenth century, the map disappeared from public knowledge until 1886, when a relatively badly preserved copy was found in a library in Munich, Germany. For more than a half-century, this map was considered to the only one in existence. However in 1962 another copy, in much better condition, was purchased on behalf of the Uppsala University Library and brought to Sweden. Little is known about the “biographies” of the two known copies and a number of questions arise as soon as one tries to find out where they come from, to whom they belonged and how they came into the possession of their previous owners. The first part of the present article takes up circumstances under which the so-called Munich copy was discovered by Oscar Brenner in 1886 and problems related to its restoration by German specialists in 1950. The second part is devoted to transactions which lead to the acquisition of the second copy by Uppsala University Library in 1962. Most of the documents related to the purchase were kept secret until recently and the opening of the sealed dossier in 2002 threw some new light on the recent history of the Carta Marina. The present investigation is focused on the enigmatic figure of Emeryk Hutten-Czapski (1897–1979), a Polish map collector, who sold an extraordinarily well-preserved copy of the Carta Marina to the Swedes. At what point and under what circumstances did he acquire the map? Where was the map kept at previous stages if its existence? Different hypotheses are examined in the light of some recently published and unpublished documents in order to trace the history of this masterpiece of Renaissance cartography.